Spatial density of Aedes distribution in urban areas: a case study of breteau index in Kuala Lumpur, Malaysia - Aziz, S.; Aidil, R.M.; Nisfariza, M.N.M.; Ngui, R.; Lim, Y.A.L.; Wan Yusoff, W.S. (Medknow Publications, 2014)
Background& Objectives: Dengue fever (DF) is a major vector-borne disease in Malaysia. The incidences of DF in Malaysia are caused by viruses transmitted through the bites of infected female Aedes albopictus and Ae. aegypti mosquitoes. This study aims to establish the spatial density of mosquito population or breteau index (BI) in the areas of Kuala Lumpur using geographic information system (GIS), remote sensing (RS) and spatial statistical tools. Method: The 2010 weekly report data of BI obtained from the Ministry of Health (MoH) and the 2010 monthly rainfall data obtained from Malaysia Meteorological Services Department were analyzed using RS and spatial statistical tools to show the spatial correlation of dengue in each zone in Kuala Lumpur. The Kernel density was implemented to identify the better dengue hotspot localities. Results: RESULTS indicated a strong significant positive relationship between the number of localities with high BI and monthly rainfall (r = 0.64; p = 0.024). In addition, types of landuse did not appear to influence the mosquito's population (Built-up: r = 0.16, p = 0.118; Cleared area: r = - 0.107, p = 0.304; Vegetation dense: r = - 0.206, p = 0.046; Vegetation sparse: r = 0.023, p = 0.823; and Water: r = 0.246, p = 0.016). Interpretation& Conclusion: In the present study, several hotspots identified will be beneficial to assist the local health authorities to reduce and eradicate mosquitoes in these areas. These results will provide valuable information through the application of advanced tools in combating Aedes mosquitoes.